All the fault of the Bourbons? The case of the 1826 forestry act - Borghetti M (Forest@, 2022)
We talk about the 1826 forestry act of the former Kingdom of the Two Sicilies, under Francis I of Bourbon. Those who talk about it, speak ill of it. The so-called “clearcut with reserves”, prescribed by the Bourbon’s act, is thought to have caused the distruction of many southern forests. Here we reason about this act, and suggest the Bourbons took several faults that were not their own. For instance, many forest cuts carried out in southern regions after the unification of Italy (under a new forestry regulatory regime) were defined, officially, as “shelterwood cuts”. However, they were nothing but “clearcut with reserves”.